DETERMINANTS OF STOCK RETURN AND IMPLICATION ON AUTOMOTIVE COMPANY VALUE IN INDONESIA - Anita Handayani; Rahmat Agus Santoso; C Candraningrat (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2022)
Stock return is something that investors and shareholders seek. Company management needs to increase the value of the company which aims to prosper the shareholders. The purpose of this research is to analyze the effect of earnings per share and debt to equity ratio on stock returns and the effect of earnings per share, debt to equity ratio, and stock returns on company value. Data analysis using multiple linear regression. The result of the research shows that for the first model only Debt To Equity Ratio has an effect , while for the second model all variables have an effect on company value . Keywords: Stock Return, Eearning Per Share, Company Value, Automotive Company